Future Directions in Research on Bryde's Whales - Constantine, Rochelle; Iwata, Takashi; Nieukirk, Sharon L.; Penry, Gwenith S. (Frontiers in Marine Science, 2018)
One of the lesser known species of baleen whales, the Bryde’s whale, also known as Eden’s whale (Balaenoptera edeni edeni and B. edeni brydei), although hunted as part of a North Pacific Japanese research programme , was not heavily exploited by commercial whaling and remains a data deficient species. Their taxonomic status is not fully resolved and they are often mistaken for other species leading to uncertainty about their true distribution, behavior and conservation status. Some populations are critically endangered, whilst others are small but have high genetic diversity suggesting wider connectivity. The species’ unpredictable coastal and offshore global distribution throughout warm-temperate waters has led to populations with unknown genetic variation, and facing different threats. Few areas are well-studied, but each study reveals often contrasting movement patterns, foraging strategies and vocal repertoires; there are considerable knowledge gaps for Bryde’s whales. There are few Bryde’s populations with abundance estimates but they typically number in the mid- to high-hundreds of individuals, with other populations small, <100 mature individuals, and exposed to high levels of anthropogenic impacts. Future research should focus on understanding the diversity within and between populations. Here, we suggest an integrative, comparative approach towards future work on Bryde’s whales, including acoustic monitoring, trophic interactions, telemetry tools, understanding their novel behaviors, and resolving their species status. This will inform conservation management of this unusual species of whale vulnerable to anthropogenic impacts.